Historitas Lembaga Pendidikan Islam di Indonesia - Ifa Afida (FALASIFA : Jurnal Studi Keislaman, 2018)
ABSTRACT Islamic education in Indonesia has been going on since the inclusion of Islam in Indonesia. In the early stages of Islamic Education begins, educational institutions have not been formed and available, seeing the beginning of the process of Islamic education that has not been systematic and emphasizes the process of da'wah carried out by preachers to their students, both personal and collective contacts. After the Muslim community was formed in an area, they began to build mosques. The mosque is functioned as a place of worship and education. The mosque is an Islamic educational institution that first appeared beside the house where the ulama or muballigh lived. After that other Islamic education institutions emerged, such as pesantren, surau, dayah. The name of the institution is different because it is influenced by differences in place, tradition and culture. But, even though the names are different, they have the same goal, namely as a process place in studying Islamic education. Furthermore, Islamic Education institutions continue to experience development in accordance with the discussions that occurred in Indonesia. KeyWords : Institutions, Islamic Education, Periodic Institutions of Islamic Education